When culture impacts health global lessons for effective health research - Banwell, Cathy; Ulijaszek, Stanley J.; Dixon, Jane (London Waltham, MA Academic Press, 2013)
Bringing the hard-to-quantify aspects of lived experience to analysis, and emphasizing what might be lost in interventions if cultural insights are absent, this book includes case studies from across the Asia and Pacific regions -Bangladesh, Malaysia, New Guinea, Indonesia, Thailand, South Korea, Australia, New Zealand, Tuvalu and the Cook Islands. When Culture Impacts Health offers conceptual, methodological and practical insights into understanding and successfully mediating cultural influences to address old and new public health issues.
When Culture Impacts Health -- Antecedents of Culture-in-Health Research -- Biological and Biocultural Anthropology -- Toward Cultural Epidemiology: Beyond Epistemological Hegemony -- The Cultural Anthropological Contribution to Communicable Disease Epidemiology -- Medicalization or Medicine as Culture? The Case of Attention Deficit Hyperactivity Disorder -- Filthy Fingernails and Friendly Germs: Lay Concepts of Contagious Disease Transmission in Developed Countries --Context and Environment: The Value of Considering Lay Epidemiology -- Identity, Social Position, Well-Being, and Health: Insights from Australians Living with Hearing Loss -- Framing Debates about Risk for Skin Cancer and Vitamin D Deficiency in New Zealand: Ethnicity, Skin Color, and/or Cultural Practice? -- Analyzing Smoking Using Te Whare Tapa Wha -- Thirty Years of New Zealand Smoking Advances a Case for Cultural Epidemiology and Cultural Geography -- On Slimming Pills, Growth Hormones, and Plastic Surgery: The Socioeconomic Value of the Body in South Korea -- Tacking between Disciplines: Approaches to Tuberculosis in New Zealand, the Cook Islands, and Tuvalu.
Includes bibliographical references and index.
Keywords: Social medicine; Health -- Social aspects